Bridging Theory, Research, and Practice in Youth Sports: Sport Psychology's Partnership with Positive Coaching Alliance to Enhance Youth Sport. Issue 1 (2nd January 2020) - Fry, Mary; Reid-Pinson, Chris; Iwasaki, Susumu; Thompson, Jim
Abstract: For 20 years, Positive Coaching Alliance (PCA) has trained adults who are currently involved in youth sport as coaches and parents to help young athletes have positive sport experiences. This article describes a new approach PCA is piloting, whereby they have partnered with a university sport psychology program to train college students in principles of positive coaching so that they may benefit directly during their college sport involvement and also leave college equipped to enhance the youth sport culture as they become youth sport coaches and parents in the future. Specifics of the partnership are presented.